2018
DOI: 10.1111/vox.12660
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation and prolonged storage of red cells are associated with increased adverse events

Abstract: Prolonged storage of irradiated RBCs was associated with a significant increase in non-allergic transfusion reactions. Overall, the irradiated RBCs appeared to cause more non-allergic reactions compared with non-irradiated RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…18 Red cell microparticles have been shown to activate both FXII and pre-kallikrein, and thus have pro-thrombotic and proinflammatory potential, 25,26 as well as activating platelets, increasing surface P-selectin and activating GPIIb/IIIa. 27,28 While these changes have not been linked to transfusion outcomes, a retrospective study found that gammairradiated RBCs were associated with more non-allergic transfusion reactions, and the frequency of non-allergic reactions increased with storage of irradiated RBCs, 29 suggesting that irradiated red cells may be more pro-inflammatory, and microparticles may potentially play a role in these reactions.…”
Section: Discussionmentioning
confidence: 99%
“…18 Red cell microparticles have been shown to activate both FXII and pre-kallikrein, and thus have pro-thrombotic and proinflammatory potential, 25,26 as well as activating platelets, increasing surface P-selectin and activating GPIIb/IIIa. 27,28 While these changes have not been linked to transfusion outcomes, a retrospective study found that gammairradiated RBCs were associated with more non-allergic transfusion reactions, and the frequency of non-allergic reactions increased with storage of irradiated RBCs, 29 suggesting that irradiated red cells may be more pro-inflammatory, and microparticles may potentially play a role in these reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published retrospective study, 71 prolonged storage of irradiated red cells was associated with a significant increase in non‐allergic transfusion reactions. Overall, the irradiated red cells appeared to cause more non‐allergic reactions compared with non‐irradiated red cells with the leading type of reaction being febrile non‐haemolytic transfusion reaction.…”
Section: Manufacturing Aspects For Irradiated Componentsmentioning
confidence: 99%
“…Table 1 displays several reports of TARs in pediatrics 1,3,5,6,13–24 . Mild ATR and FNHTR account for the majority of TARs, similar to the frequencies observed among adults 2,5,6,25,26 . Severe life‐threatening side effects such as anaphylactic shock, hypotensive reaction, TRALI, TACO, and other TARs have also been reported with some frequency 1–6,13 .…”
Section: Outline Of the Onset Of Transfusion‐associated Adverse React...mentioning
confidence: 68%
“…1,3,5,6,[13][14][15][16][17][18][19][20][21][22][23][24] Mild ATR and FNHTR account for the majority of TARs, similar to the frequencies observed among adults. 2,5,6,25,26 Severe life-threatening side effects such as anaphylactic shock, hypotensive reaction, TRALI, TACO, and other TARs have also been reported with some frequency. [1][2][3][4][5][6]13 Generally, TARs are likely caused by platelet (PLT) products that are particularly prone to cause mild ATR.…”
mentioning
confidence: 99%